Günümüz heykel sanatında soyut form ve malzeme ilişkisi - Bakkal, Hülya (My University, 2019)
ÖZETGÜNÜMÜZ HEYKEL SANATINDA SOYUT FORM VE MALZEME İLİŞKİSİBu tez çalışması, heykel sanatında soyut eğilimlerin malzemesiyle kurduğu ilişkiyi incelemiştir. Tez, günümüzde heykeltıraşları yeniden soyut forma yönlendiren sebepleri, geçmiş pratiklere göre nasıl ve hangi yönden yeni biçim ve içerikler ürettikleri ve bu yeni olan yaklaşımların kültürel alanda bir karşılık oluşturup oluşturmadığı sorularına yanıt bulmaya çalışmıştır. Malzemenin seçimi ve kullanım teknikleri üzerinden soyut formu değerlendirmek tezin sorunsalını çözümlemede doğru bir veri olarak kabul edilmiş ve tezin konusunu belirlemiştir.Eser-metin olarak hazırlanan çalışma geçmiş, günümüz ve eser metni oluşturan üretimlerin irdelendiği üç ana başlık altında toplanmıştır. Birinci bölümde XX. yüzyılda soyut form ve malzeme ilişkisi, farklı formalist üslupların ele alındığı alt başlıklarda incelenmiştir. Günümüz heykelinin irdelendiği ikinci bölüm ‘yeni formalizm’ tanımı altında ele alınmıştır. Üçüncü bölümde ise eser metne dahil üretimlerin biçim, malzeme ve içerik ilişkisi değerlendirilmiştir. Bu araştırma ve incelemeler ışığında günümüz sanatında malzeme seçimi ve kullanım biçimiyle soyut formun yeniden ele alındığı sonucuna varılmıştır. Günümüz heykelinde soyut form, yeni malzemeler yardımıyla yeni içerikler ve bakışlar yaratmaktadır. Yeni formalist yaklaşım günümüzde değişen ve devinen toplumsal ve kültürel yapıyı anlamak için heykelin önemli bir mecra olarak değerlendirilmesine imkân sunmaktadır.

SUMMARYTHE RELATION OF ABSTRACT FORM AND MATERIAL IN CONTEMPORARY ART OF SCULPTUREThe thesis studies the relationship between the abstract trends and their materials in the art of sculpture. The thesis tries to find answers to the questions such as the reasons that redirects the sculpturers to the abstract form and how and on which aspects they create the new forms and contents in terms of older practices and whether these new approaches match in the cultural zone, or not. The assessment of the abstract form through the material selection and the style of use has been adopted as the accurate data for analyzing the problematic of the thesis, and has determined the subject matter of the thesis.The study prepared as work-text have been compiled in three main topics which discuss the past, today and the artistic creations constituent the work-text. In the first part, the relation of form and material in the 20th Century is studied in the subparts of different formalist genres have been discussed. The second part investigating the contemporary sculpture is discussed with a description of ‘New formalism’. In the third part, the relationships between form, material and content in the artistic creations included in the work-text are interpreted. In the light of these research and studies, it is decided that the abstract form is reconsidered with its selection and use of material in today’s art. The abstract form creates new contents and visions with the help of its new materials in today’s sculpture. The new formalist approach provides an opportunity to assess the importance of sculpture as an important media to understand today’s changing and moving social and cultural structure.
Keywords: Abstract Form; Abstract Sculpture; Contemporary Art of Sculpture; Form and Material Relationship; Form ve Malzeme İlişkisi Sculpture; Formalism; Formalizm; Günümüz Heykel Sanatı; Heykel; Heykel Sanatı; Heykeltraşlık, Modern; Modern Heykel; Modern Sculpture; New Formalism; Sculpture, Modern; Soyut Form; Soyut Heykel; The Art of Sculpture; Turkish Abstract Sculpture; Türk Soyut Heykeli; Yeni Formalizm